2005
DOI: 10.4315/0362-028x-68.9.1804
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle-Antibody Conjugates for the Separation of Escherichia coli O157:H7 in Ground Beef

Abstract: The immunomagnetic separation with magnetic nanoparticle-antibody conjugates (MNCs) was investigated and evaluated for the detection of Escherichia coli O157:H7 in ground beef samples. MNCs were prepared by immobilizing biotin-labeled polyclonal goat anti-E. coli antibodies onto streptavidin-coated magnetic nanoparticles. For bacterial separation, MNCs were mixed with inoculated ground beef samples, then nanoparticle-antibody-E. coli O157:H7 complexes were separated from food matrix with a magnet, washed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(99 citation statements)
references
References 27 publications
2
97
0
Order By: Relevance
“…Recently, a new method that is referred to as immunomagnetic separation was developed to effectively isolate pathogens from food matrices using magnetic pellets to functionalize antibodies against target pathogens (Varshney et al, 2005). A similar technique was reported that is based on magnetic nanoparticles with a diameter of 30 nm functionalized with anti-L. monocytogenes antibodies via biotin-streptavidin bonds to generate immunomagnetic nanoparticles that were shown to capture L. monocytogenes during a 2-h immunoreaction (Damira et al, 2012).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a new method that is referred to as immunomagnetic separation was developed to effectively isolate pathogens from food matrices using magnetic pellets to functionalize antibodies against target pathogens (Varshney et al, 2005). A similar technique was reported that is based on magnetic nanoparticles with a diameter of 30 nm functionalized with anti-L. monocytogenes antibodies via biotin-streptavidin bonds to generate immunomagnetic nanoparticles that were shown to capture L. monocytogenes during a 2-h immunoreaction (Damira et al, 2012).…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
“…Mass-sensitive biosensors are utilized less frequently than optical and electrochemical biosensors (Su and Li, 2005). Also known as piezoelectric biosensors, they use piezoelectric crystals that are highly sensitive and can detect small changes in mass.…”
Section: Mass-sensitive Biosensorsmentioning
confidence: 99%
“…When attached to antibodies these are used for immunogenic separation of bacteria, viruses, proteins and nucleic acid. Li and his co-workers used antibody conjugated nanoparticles to isolate Escherichia.coli O157:H7 from ground beef (Varshney, Yang, Su, & Li, 2005). Magnetic nanoparticles conjugates with proteins and microbes are used in detoxification of bio fluids, tissue repair, immuno-assay cell separation, and hyperthermia and drug delivery.…”
Section: Magnetic Nanoparticle Sensorsmentioning
confidence: 99%
“…CFU/ml in ground beef [37] Amperometric E. coli, L. monocytogenes, and C. jejuni Without pre-enrichment 10-50 Cells/ml in milk and ground chicken [38] Amperometric Vibrio After 24hrs pre-enrichment 7.3 × 10 4 CFU/ml in culture media [39] Amperometric E. coli After 24hrs pre-enrichment 5 × 10 4 CFU/ml in wastewater [40] Amperometric E. coli Without pre-enrichment 55 Cells/ml, 100 Cells/ml in buffer solution and milk, respectively [41] Potentiometric E. coli O157:H7 After 24hrs pre-enrichment 10 4 CFU/ml in buffer solution [42] Potentiometric E. coli After 30hrs pre-enrichment 10 Cells/ml in ground vegetable [32] Impedimetric E. coli O157:H7 After 24hrs pre-enrichment 2 CFU/ml in culture media [43] Impedimetric E. coli O157:H7 Without pre-enrichment 83.7 CFU/ml in milk [44] Impedimetric Listeria…”
Section: 배양 및 콜로니 기반의 방법mentioning
confidence: 99%